Clinical and Biological Factors Affecting Left Ventricular End-Diastolic Pressure in ST-Segment Elevation Myocardial Infarction - Sadiq, Muhammad Wajid; Siddique, Muhammad Bilal; Farhan, Shaheer; Ahmed, Iftikhar; Haider, Riaz; Shahzad, Malik Muhammad Khurram (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the clinical & biological factors affecting Left Ventricular End Diastolic Pressure(LVEDP) in ST-Segment Elevation Myocardial Infarction (STEMI) patients undergoing coronary angiography followed by Primary Percutaneous Coronary Intervention(PPCI).Study Design: Quasi-Experimental study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Feb-Aug 2024.Methodology: Ninety-six STEMI patients regardless of gender were enrolled through consecutive sampling. Baseline variables like Hs-Trop I, BMI, Ejection Fraction, Mean Arterial Pressure, and Killip Class were noted upon patient arrival at emergency room. LVEDP was measured using pigtail catheter during coronary-angiography and patients were classified non-randomly in two Groups: LVEDP